Auxiliary Liver Graft Can Be Protected From HBV Infection in HBsAg Positive Blood Circulation - Wei, Lin; Zhang, Hai-Ming; Wan, Chi-Dan; Qu, Wei; Zeng, Zhi-Gui; Liu, Ying; Xiong, Jun; Sun, Li-Ying; Zhu, Zhi-Jun (Frontiers in Medicine, 2021)
Auxiliary grafts have a high risk of Hepatitis B virus (HBV) infection in patients with chronic HBV-related diseases. Hepatitis B virus-related auxiliary partial orthotopic liver transplantation (APOLT) cases were reviewed to show the results of current methods to block native-to-graft HBV transmission. Three patients received APOLT for HBV-related liver cirrhosis and a recurrent upper gastrointestinal hemorrhage between April 2015 and January 2017 by the liver transplant team of Beijing Friendship Hospital affiliated with Capital Medical University. All three patients were positive for HBV surface antigen (HBsAg) and had a negative HBV DNA test result before transplantation. After auxiliary transplantations, HBsAg was found to be positive in two patients and negative in one patient. To avoid graft infection of HBV, entecavir-based therapy was employed and the remnant native livers of the recipients were removed 51–878 days after liver transplantation. Then, serum conversions of HBsAg were found in all three cases. For the first time, this case series shows the possibility of blocking the transmission of HBV from a native liver to a graft in auxiliary transplantation by entecavir-based therapy. Among the cases, a left lobe graft was successfully implanted as a replacement of the right lobe of the recipient, which is also discussed.